2018
DOI: 10.18203/2320-1770.ijrcog20180869
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of DIPSI and IADPSG criteria for diagnosis of GDM

Abstract: GDM is defined as any degree of glucose intolerance with onset or first recognition during pregnancy. The prevalence of GDM varies, widely based on the diagnostic criteria used and the ethnic group studied. It is associated with adverse maternal and perinatal outcome. Incidence of GDM in India is 1-14%. There are several screening and diagnostic tests for GDM. It is important to diagnose early and treat to prevent these complications. The present study was done to compare Diabetes in Pregnancy Study Group Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…An Indian study found that sensitivity and specificity of DIPSI was 45% and 87% whereas for IADPSG it was 40% and 89% respectively, the sensitivity of DIPSI was better when compared to IADPSG criteria. The study finding highlighted that in all pregnant women GDM screening GDM is mandatory due its increasing prevalence in India [23]. Similar finding was observed by Geetha et al, where 14% and 9% were diagnosed by DIPSI and by IADPSG respectively, whereas 4% were diagnosed by both criteria.…”
Section: Advantage Of Dipsi Criteria Over Other Methodssupporting
confidence: 86%
“…An Indian study found that sensitivity and specificity of DIPSI was 45% and 87% whereas for IADPSG it was 40% and 89% respectively, the sensitivity of DIPSI was better when compared to IADPSG criteria. The study finding highlighted that in all pregnant women GDM screening GDM is mandatory due its increasing prevalence in India [23]. Similar finding was observed by Geetha et al, where 14% and 9% were diagnosed by DIPSI and by IADPSG respectively, whereas 4% were diagnosed by both criteria.…”
Section: Advantage Of Dipsi Criteria Over Other Methodssupporting
confidence: 86%
“…They concluded that screening is very essential in all pregnant women due to high prevalence of GDM in India and sensitivity of DIPSI was better than IADPSG criteria. 19 Similarly, in the study Geetha et al, 14% were diagnosed by DIPSI criteria, 9% were diagnosed by IADPSG criteria and 4% were diagnosed by both. Diagnosis of GDM by IADPSG criteria leaves 5% undiagnosed, which may be easily detected through DIPSI.…”
Section: Discussionmentioning
confidence: 83%
“…11 Srinivasan et al in their study found prevalence of GDM using DIPSI and IADPSG criteria to be 17.4% and 15.3% respectively. 12 In a prospective study of 100 women Geetha et al found prevalence rates of GDM to be 14% and 9% with DIPSI and IADPSG criteria respectively. In the same study they found that 4% were diagnosed by both criteria and 5% were left undiagnosed by IADPSG criteria which could have been easily detected by DIPSI.…”
Section: Discussionmentioning
confidence: 98%